The Relevance of Progressive Education to Islamic Education in the Millennial Era - Anisa, Fira Nur; Suwendi, Suwendi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study explores the relevance of progressive education principles to Islamic education in addressing the challenges of the millennial era. Using a qualitative literature review and content analysis approach, the research applies John Dewey’s progressive educational theory as the primary framework. Findings reveal that the core principles of progressive education, including democratic learning, problem-solving, and experiential knowledge, align closely with Islamic education's objectives. These principles emphasize student-centered learning, integration of real-life experiences, and the harmonious development of intellectual and spiritual capabilities. The study highlights the potential of progressive Islamic education to merge traditional values with modernization, fostering critical thinking, creativity, and adaptability in students. By integrating democratic values, collaborative learning, and problem-solving skills, Islamic education can remain dynamic and relevant to the rapidly evolving global context. This research contributes to the discourse on educational reform, demonstrating how Islamic education can adapt to contemporary challenges while preserving its foundational ethos.